Pemberdayaan Infak Air Galon Sebagai Wujud Pengabdian Kepada Masyarakat di Kampung Bojong Talang Desa Cibadak Kecematan Cibadak Kabupaten Sukabumi - Taufik CH; Haris, Ahmad; Ibnussabil, Ibnussabil; Aziz, Muazam Saikhul; Ansory; Zikrullah, Mohammad (Zad Al-Ummah: Jurnal Pengabdian Masyarakat, 2024)
This service aims to analyze the impact of the gallon water infaq empowerment program on the lives of villagers in terms of health and socio-culture. The methods used include participatory observation, in-depth interviews with stakeholders, and secondary data analysis. The availability of clean water is one of the basic needs of the community that is still a challenge in some areas. The Infak Air Galon program is a community service initiative that aims to help meet the needs of clean water for the community with the main objective of serving the community. Through the Infak Air Galon program, donors participate by donating water filtration equipment which is then distributed to the local community through several procedures. The implementation of this activity involves cooperation between the community service team from KKN group 2 STIQ Zad Cianjur students and is supervised by the foundation that manages the water filtration equipment.